European Academy of Neurology guideline on trigeminal neuralgia. (8th April 2019) - Bendtsen, L.; Zakrzewska, J. M.; Abbott, J.; Braschinsky, M.; Di Stefano, G.; Donnet, A.; Eide, P. K.; Leal, P. R. L.; Maarbjerg, S.; May, A.; Nurmikko, T.; Obermann, M.; et al.
Abstract : Background and purpose: Trigeminal neuralgia (TN) is an extremely painful condition which can be difficult to diagnose and treat. In Europe, TN patients are managed by many different specialities. Therefore, there is a great need for comprehensive European guidelines for the management of TN. The European Academy of Neurology asked an expert panel to develop recommendations for a series of questions that are essential for daily clinical management of patients with TN. Methods: A systematic review of the literature was performed and recommendations was developed based on GRADE, where feasible; if not, a good practice statement was given. Results: The use of the most recent classification system is recommended, which diagnoses TN as primary TN, either classical or idiopathic depending on the degree of neurovascular contact, or as secondary TN caused by pathology other than neurovascular contact. Magnetic resonance imaging (MRI), using a combination of three high‐resolution sequences, should be performed as part of the work‐up in TN patients, because no clinical characteristics can exclude secondary TN. If MRI is not possible, trigeminal reflexes can be used. Neurovascular contact plays an important role in primary TN, but demonstration of a neurovascular contact should not be used to confirm the diagnosis of TN. Rather, it may help to decide if and when a patient should be referred for microvascular decompression. In acute exacerbations of pain, intravenous infusion of fosphenytoin or lidocaine can be used. For long‐term treatment, carbamazepine or oxcarbazepine are recommended as drugs of first choice. Lamotrigine, gabapentin, botulinum toxin type A, pregabalin, baclofen and phenytoin may be used either alone or as add‐on therapy. It is recommended that patients should be offered surgery if pain is not sufficiently controlled medically or if medical treatment is poorly tolerated. Microvascular decompression is recommended as first‐line surgery in patients with classical TN. No recommendation can be given for choice between any neuroablative treatments or between them and microvascular decompression in patients with idiopathic TN. Neuroablative treatments should be the preferred choice if MRI does not demonstrate any neurovascular contact. Treatment for patients with secondary TN should in general follow the same principles as for primary TN. In addition to medical and surgical management, it is recommended that patients are offered psychological and nursing support. Conclusions: Compared with previous TN guidelines, there are important changes regarding diagnosis and imaging. These allow better characterization of patients and help in decision making regarding the planning of medical and surgical management. Recommendations on pharmacological and surgical management have been updated. There is a great need for future research on all aspects of TN, including pathophysiology and management. Abstract : Click here for the corresponding questions to this CME article.